Karakteristik Membran Komposit Poli Eter Eter Keton Tersulfonasi untuk Direct Methanol Fuel Cell - Nur Hidayati (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Fuel cell is a device that transforms chemical energy into electrical energy through oxidation-reduction reaction of hydrogen-rich fuel with oxygen or air. Direct Methanol Fuel Cells (DMFC) as a proton exchange membrane fuel cell is potentially developed to realize the commercialization of fuel cells in transportation applications. Membrane that is currently widely used for DMFC is Nafion®. However Nafion® membrane has disadvantages such as high price, short-lived and high methanol permeability. Poly Ether Ether Ketone (PEEK) is an alternative material due to having good combinations of physico-chemical and mechanical properties but it is hydrophobic material, therefore it has very low ionic conductivity. This research aims to study the effect of the addition of cesium- phosphotungstic acid (1-15w.% loading) to the sulfonated PEEK (sPEEK) membrane. The analysed characteristics were water uptake, swelling degree, methanol permeability and ionic conductivity. Increased loading of cesium- phophotungstic acid into sPEEK membranes improved the value of water uptake, swelling factor and ionic conductivity. Moreover the methanol permeability through the composite membrane was fortunately reduced up to 9% loading and then increased when the percentage of loading was raised up. Proton conductivity was increased up to 10% loading and lowered at more loading.